The Impact of Flipped Learning Strategy on the Achievement of Tenth-Grade Students in Arabic Language Subject in Jordan - Zuhair Ahmed Al-Hasanat (Britain International for Academic Research (BIAR) Publisher, 2022)
The study aimed to find out the impact of the Flipped education strategy on the achievement of tenth-grade students in the basic Arabic language subject in Jordan. The study sample consisted of (69) basic tenth-grade students distributed among two divisions randomly, one division was randomly selected to represent the experimental group, consisting of (33) students studied using the Flipped learning strategy, and the other division represented the control group, consisting of (36) students studied in the usual way. The study results showed that there are significant differences between the average performance of students in the experimental and control groups on the dimensional Achievement Test in favor of the experimental group, and the study recommended that teachers of the Arabic language should adopt the Flipped learning strategy as a teaching method because of its impact on achievement.